PEMANFAATAN ALAT PENGERING DARI DRUM BEKAS DENGAN BAHAN BAKAR GAS UNTUK PEMBUATAN ASAM SUNTI DI GAMPONG PAYA BUJOK TUNONG - Iskandar; Harmin, Amalia; Isra, Muhammad; Fauzan, Fauzan; Bravikawati, Marini (Jurnal Masyarakat Berdikari dan Berkarya (Mardika), 2025)
The plant with the Latin name Averhoa Bilimbi L or better known as belimbing wuluh is one of the vegetable plants that is widely used as a seasoning for dishes, one of which is sunti acid, which is the result of drying from belimbing wuluh. The star fruit plant also bears fruit throughout the year. The people of Aceh, especially the people of Gampong Paya Bujok, utilize dried star fruit into sunti acid for cooking spices. Inefficient drying will affect drying, for example weather factors and the length of the drying process caused by sunlight not being obtained for 24 hours. The purpose of this community service is to obtain an efficient drying process and hygiene of the product by utilizing a dryer from a used gas-fueled drum. The plant with the Latin name Averhoa Bilimbi L or more commonly known as belimbing wuluh is one of the vegetable plants that is widely used as a seasoning for dishes, one of which is sunti acid, which is the result of drying from belimbing wuluh. The star fruit plant also bears fruit throughout the year. The people of Aceh, especially the people of Gampong Paya Bujok, utilize wuluh starfruit which is dried into sunti acid for seasoning dishes. Drying that is less efficient will affect drying, for example weather factors and the length of the drying process caused by sunlight that is not full 24 hours. The purpose of this community service is to get an efficient drying process and hygiene of the product by using a dryer from a gas-fueled used drum.